Restoration of Soil Physical and Chemical Properties of Abandoned Tin- Mining in Bangka Belitung Islands - Yuarsah, Ishak; Handayani, Etik Puji; Rakhmiati, .; Yatmin, . (JOURNAL OF TROPICAL SOILS, 2017)
The practices of tin mining which removing all layers of soil on deposits of minerals caused the seriously environmental problems, i.e degradation of physical and chemical soil, disappearance of vegetation, flora and fauna in ecosystems that changed the microclimate. In the tailings area of tin mining have unstable structure, the content of organic matter is very low, so it is vulnerable to land slides and erosion. The characteristic of tailing area that very acid, low nutrient availability, low water storage and high soil temperature are constraints in the conservation and improvement this area. The aim of this research was found conservation technology to improve the properties ofÂ  soil on Tin mining land due to human activities that cause environmental damage both micro and macro so determination of plant species and specific location technology can be done based on characterization and potential evaluation soil resources. Annual crop cultivation and cultivation of legume cover crop (Mucuna sp., Long-lived, Calopogonium sp., Peuraria javanica) and management of top soil and organic matter are a must, in addition to improve soil structure, maintaining soil moisture, as well as to reduce the loss nutrients, as inÂ  textured rough soil (sandy) nutrients in soil are easily washed.Keywords: Characteristic soil, improvement, tailing area, tin mining